Advances in Malaria Diagnostic Methods in Resource-Limited Settings: A Systematic Review. - Prah, D.A.; Nii-Trebi, N.I.; Anim-Baidoo, I.; Amegatcher, G.; et al. (Tropical Medicine and Infectious Disease, 2024)
Malaria continues to pose a health challenge globally, and its elimination has remained a major topic of public health discussions. A key factor in eliminating malaria is the early and accurate detection of the parasite, especially in asymptomatic individuals, and so the importance of enhanced diagnostic methods cannot be overemphasized. This paper reviewed the advances in malaria diagnostic tools and detection methods over recent years. The use of these advanced diagnostics in lower and lower-middle-income countries as compared to advanced economies has been highlighted. Scientific databases such as Google Scholar, PUBMED, and Multidisciplinary Digital Publishing Institute (MDPI), among others, were reviewed. The findings suggest important advancements in malaria detection, ranging from the use of rapid diagnostic tests (RDTs) and molecular-based technologies to advanced non-invasive detection methods and computerized technologies. Molecular tests, RDTs, and computerized tests were also seen to be in use in resource-limited settings. In all, only twenty-one out of a total of eighty (26%) low and lower-middle-income countries showed evidence of the use of modern malaria diagnostic methods. It is imperative for governments and other agencies to direct efforts toward malaria research to upscale progress towards malaria elimination globally, especially in endemic regions, which usually happen to be resource-limited regions.
Research Article
Keywords: Malaria; Polymerase Chain Reaction (PCR); Loop-Mediated Isothermal Amplification (LAMP); Diagnostic Methods